Decoding Mixed Connective Tissue Disease in Bahrain: Clinical and Serological Characteristics - Adla B. Hassan (Journal of Intelligent Decision Making and Information Science, 2026)
Background. The global epidemiology of mixed connective tissue disease (MCTD) remains elusive due to its diverse clinical manifestations and limited number of reported cases. Data from the Middle East, particularly the Gulf region and Bahrain, are especially scarce. Objectives. The current study aimed to fill the gap in MCTD research by providing novel insights into the clinical features, and serological profile of MCTD in Bahrain.Methods. This is a retrospective multicenter cross-sectional study. MCTD patients followed at three big hospitals in Bahrain during the period 2013-2022 were included. Demographic, clinical, serological, and therapeutic data were collected for analysis using Python (version 3.11).Results. This study included 69 patients with MCTD and 54 with SLE. The median age of MCTD patients was 38 years (MAD±12.0; range 18–71), with a female predominance (82.6%). The most common clinical manifestations among MCTD patients were fatigue (66.7%), arthritis (52.2%), myalgia (31.9%), muscle weakness (26.9%), skin rash (20.3%), and Raynaud’s phenomenon (15.9%). Concerning systemic manifestations, neuropsychiatric symptoms (57.7%) were prominently noted, followed by pulmonary complications. All MCTD patients (100%) were positive for anti-U1-RNP antibodies, with 61% demonstrating high titers (≥1:1600). In contrast, titers of anti-ds-DNA (30%), anti-Ro/SSA (41%), and anti-Smith (23%) antibodies were generally low. Notably, elevated anti-U1-RNP titers correlated positively with heart failure and peripheral neuropathy.Conclusions: This study highlights distinct clinical and serological features of MCTD in the Bahraini population, emphasizing disease heterogeneity. Comprehensive serological profiling, alongside clinical evaluation, may improve diagnosis and the early identification of patients at risk of severe complications.